THE GLOBAL READING STRATEGY ON READING COMPREHENSION ACHIEVEMENT AMONG ELEVENTH GRADE STUDENTS (English Community Journal, 2022)
Numerous researches have been undertaken over the last several decades to evaluate the knowledge of the usage of reading strategies. However, this study has primarily focused on the impact of the Global Reading Strategy on students' reading comprehension achievement. The population in this study was eleventh-grade students of SMA Muhammadiyah 1 Palembang in the academic year 2021/2022, the sample was 64 students collected as the representative of 347 students. This study was a quantitative descriptive study. The data was collected using a questionnaire and a test, and then analyzed using correlational (Spearman rho) and regression analysis. SPSS Software22 was used to calculate the test results. The results revealed a substantial association (r =.878) between students' reading techniques and their reading comprehension achievement. Reading techniques influenced reading comprehension achievement by 0.759 percent, or 75.9%. Meanwhile, the F-test revealed that the F-obtained was 195.152 with a significant level of p 0.05, which was higher than the F-table value of 3.99. The alternative hypothesis (Ha) was accepted while the null hypothesis (Ho) was rejected since the F-obtained was higher than the F-table. It suggests that students' reading techniques had a significant influence on reading comprehension achievement among Eleventh-Grade students at SMA Muhammadiyah 1 Palembang.